Green Sukuk Retail Towards Sustainable Development in Indonesia - Atika Zahra Maulida; Noormailati; Agus Purnomo (Islamic Economics Journal, 2023)
Green Sukuk is one of the products in the Sharia capital market that wants to be developed to encourage the country's economic growth by applying Sharia principles. Green sukuk buying and selling transaction agreement using wakalah contract and ijarah. The issuance of Green Sukuk on retail sukuk products issued by issuers can encourage the country's economic growth. This study aims to determine the development and economic growth through green sukuk products in retail sukuk products. This research uses qualitative methods with a literature review approach from previous research. The data collection method examines previous research in articles and progress reports, transactions, and economic growth from 2019 to 2022. The results of the data that have been collected will be used to answer the growth and development of green sukuk transactions on ST0060 retail sukuk products issued by the government and by private companies. The study's results explain that the performance improvement in retail sukuk products has increased yearly. The performance of the Net Asset Value of retail sukuk (green sukuk) NAV in 2019 increased by 3.56%; in 2021, the performance value of the Net Asset Value of Bersi h decreased by 2.83% due to the impact of the Covid-19 pandemic. In FY2022, the performance value of net assets increased by 41% due to stable economic performance. The role of government encouragement and economic performance growth has an impact on increasing Sharia capital market investors in retail sukuk products in 2022. The impact of performance, growth, development, and transaction growth on retail sukuk ST006 can be illustrated in the pattern. The graph shows a positive direction affecting the country's economic growth.